Research of Multi- Objective Optimization Design for Car Main Reduction Gear based on Response Surface Method - Zhou Dan (Jixie chuandong)
In order to obtain the effects of size parameters on meshing performance of the main reduction gear in a car,the response parameters of gear meshing are obtained by using the explicit finite element method.The response surface model of meshing response parameters of thegear size parameters are established based on the Kriging model. The main reducing gear parameter optimization are carried out by using the NSGA- Ⅱ multi- objective optimization genetic algorithm in which the tooth root bending stress,tooth surface contact stress and volume of the gears are defined as objective function,the solution set of the gears parameters are obtained. The meshing stress level of main reduction gears decreased significantly after the optimization.